Lichen planus in children: A retrospective study in 76 patients at a tertiary care center in South India - Shilpashree P Ravikiran; Ashok Kumar Jaiswal; Y G Anupama; N T Madan Mohan; Pavan Kumar Reddy (Wolters Kluwer Medknow Publications, 2017)
Introduction: Lichen planus (LP) is a chronic inflammatory pruritic dermatosis occurring infrequently in children. Very few studies are available on childhood LP from South India. Aim: This study aims to analyze the clinical profile of LP among children. Settings and Design: This was a retrospective study. Materials and Methods: Records of the children <16 years with LP attending our tertiary care center from January 2011 to April 2016 were tabulated and analyzed. Results: Of the 76 children with childhood LP, examined over a period of 5.4 years, 42 were boys and 34 were girls with a male: female ratio of 1.2:1. Childhood LP accounted for 17.7% of total LP cases. The mean age of the children was 10.7 years, and the lesions appeared earlier in boys than girls. Limbs were the common site of onset, and classical LP was observed in 56.6% (43) of cases followed by, linear LP (11, 14.4%), hypertrophic LP (10, 13.2%), eruptive LP, and actinic LP in 5.3% each. Koebner's phenomenon was noted in 37.3% and a positive history of infective foci before the onset was noted in 14.4% of children. Palmoplantar, oral mucosal, and nail involvement were noted in 7.8%, 14.4%, and 15.7% of children, respectively. Multiple morphological types were noted in 14.4% of children. Conclusion: Hence, as per our study, LP in children is relatively common, and it can sometimes be triggered by infection. Apart from classical LP, linear LP, annular LP, and palmoplantar involvement were frequently observed in the present study.